Creating social value through social entrepreneurship - Afacan Findikli, Mine, 1971-; Acar Erdur, Duygu, 1985- (Advances in business strategy and competitive advantage., 2021)
"The book helps readers understand the role of social entrepreneurship in creating social value and highlights the importance of social entrepreneurs in emerging economies through investigation of topics such as social value, social impact, social entrepreneurship ecosystem, triggers and challenges of social entrepreneurship, social entrepreneurship in emerging economies"--